Phenological Monitoring at Royal Botanic Garden Edinburgh - Harper, Geoff; Mann, David; Thomson, Roy (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2004)
Phenological monitoring at the Royal Botanic Garden Edinburgh (RBGE) began in the mid 19th century, and is now being developed as a number of projects. In view of the wide range of plantclimate interactions, it is recommended that projects are designed with clear and limited objectives, and are then conducted consistently and to a high standard over a long period. The projects at RBGE are outlined, and the suitability of botanic gardens in general for phenology is discussed. A distinction is drawn between ’organism phenology’ and ’population phenology’, and also between ’extensive’ and ’intensive’ approaches to project design. The variety of possible projects is illustrated by a number of completed and on-going projects in the UK, USA and northern Eurasia. It is suggested that botanic gardens can enhance their service to society by becoming phenological monitoring stations.